Activity of Brazilian propolis against Aeromonas hydrophila and its effect on Nile tilapia growth, hematological and non-specific immune response under bacterial infection - Orsi, Ricardo O. [UNESP]; dos Santos, Vivian G. [UNESP]; Pezzato, Luiz E. [UNESP]; de Carvalho, Pedro L. P. F. [UNESP]; Teixeira, Caroline P. [UNESP]; Freitas, Jakeline M. A. [UNESP]; Padovani, Carlos R. [UNESP]; Sartori, Maria M. P. [UNESP]; Barros, Margarida Maria [UNESP] (FapUNIFESP (SciELO), 2017)
The effect of the ethanolic extract of propolis (EEP) on Aeromonas hydrophila was analyzed by determination of minimum inhibitory concentration (MIC). Then, the effects of crude propolis powder (CPP) on growth, hemato-immune parameters of the Nile tilapia, as well as its effects on resistance to A. hydrophila challenge were investigated. The CPP (0.5, 1.0, 1.5, 2.0, 2.5 and 3.0%) was added to the diet of 280 Nile tilapia (50.0 ± 5.7 g fish-1). Hemato-immune parameters were analyzed before and after the bacterial challenge. Red blood cell, hematocrit, hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), and hydrogen peroxide (H2O2) and nitric oxide (NO) were evaluated. The MIC of the EEP was 13% (v/v) with a bactericidal effect after 24 hours. Growth performance was significantly lower for those fish fed diets containing 2.5 and 3% of CPP compared to the control diet. Differences in CPP levels affected fish hemoglobin, neutrophils number and NO following the bacterial challenge. For others parameters no significant differences were observed. Our results show that although propolis has bactericidal properties in vitro, the addition of crude propolis powder to Nile tilapia extruded diets does not necessarily lead to an improvement of fish health.
Keywords: Health; Hematology; Immunology; Oreochromis niloticus; Propolis; Stress